Estimation of Soil Erosion as a Function of Land Use and Rainfall Using rMMF Model on Amukura Hills, Busia County - Waswa, M. B.; Kollongei , J. K.; Mutai, E. B. K. (Africa Environmental Review Journal, 2022)
Soil erosion by water is considered as the most critical problem on cultivated steeply sloping lands in Kenya. On the Amukura hills in Busia County, Kenya, there have been increased farming activities and indiscriminate infrastructural expansions which are affecting the biophysical environment of the area. The aim of this study was to estimate the amount of soil loss as a synergistic action of rainfall and land use on the hills using the revised Morgan Finney model and compare model generated soil erosion with that obtained from field measurements. One topo-sequence was selected for validating the model. Current soil loss was determined by measuring the dimensions of rills and multiplying the average width, depth and length to get actual volume of soil moved. The model was chosen because of its simplicity in structure, low input requirements semi-empirical basis and distributed application. The equations comprising the model were translated into Microsoft excel spread and the input parameters measured from the field and weather station used. The model calculations were based on daily rainfall time steps and the results presented here were a sum of individual rainfall events. While any amount of Hortonian flow is erosive, it was found that all the detached soil particles go into transport at a rainfall intensity of 7mm/hr in this watershed. The model estimated soil loss was 17 t/ha to 50 t/ha while that from field measurement was 11 t/ha to 107 t/ha for the period studied. There was a positive correlation between field measured and model generated soil loss. The model continuously generated soil erosion data and can be applied to other areas with steep slopes and can be used to extrapolate past and future soil erosion rates based on rainfall, land use and soil properties. On the steep slopes where cultivation has taken place mechanical soil erosion control measures such as terraces and contour stone bunds along with orchard trees should be undertaken.